A divulgação dos benefícios pós-emprego: um estudo nas empresas do Índice IBOVESPA - Bandoni, Raquel (2017)
The present work aims at analyzing the disclosure of post-employment benefits made by Brazilian companies listed in the IBOVESPA index, at BMF&BOVESPA, from 2009 to 2016. The Standardized Financial Statements of those companies were analyzed, searching for information published according to a checklist prepared in agreement with each CPC 33 (R1) paragraph referring only to the post-employment benefits, either qualitative or quantitative. The data for this study were obtained through content analysis of explanatory notes inside the referred financial statements in the period analyzed, for all entities that belonged to the sample. The data were afterwards either filled in a spreadsheet, and then calculated in the percentage of the total or displayed in graphics. The results showed that there was a consistent increase in the accomplishment of the disclosure requirements from 2009 to 2016, and that between the two classifications susceptible to be framed for referred benefits, the defined contribution ones are widely spread by the companies, which may provide a better understanding and knowledge of CPC 33(R1) rules. For those framed in the defined benefit characteristics, apart from a bigger complexity observed in the rule, some items still need disclosure evolution by part of the analyzed sample, such as: (i) description of the responsibility by the plan and risks management; (ii) disclosure of asset ceiling and segregation of actuarial profits and losses between demographic and financial premises; (iii) segregation between contributions made by the employer and participants; and (iv) strategies of confrontation among assets and liabilities and cost politics. We expect that the results of this research can contribute for the comprehension of the rule and which of its elements are important to be part of professional trainings and the disclosure base of the Financial Statements of big companies, showing relevant information about the financial health of these plans